Clinical, socio‐demographic and psychological characteristics in individuals with persistent psychotic experiences with and without a "need for care". Issue 1 (February 2016) - Peters, Emmanuelle; Ward, Thomas; Jackson, Mike; Morgan, Craig; Charalambides, Monica; McGuire, Philip; Woodruff, Peter; Jacobsen, Pamela; Chadwick, Paul; Garety, Philippa A.
Abstract : Individuals reporting persistent psychotic experiences (PEs) in the general population, but without a "need for care", are a unique group of particular importance in identifying risk and protective factors for psychosis. We compared people with persistent PEs and no "need for care" (non‐clinical, N=92) with patients diagnosed with a psychotic disorder (clinical, N=84) and controls without PEs (N=83), in terms of their phenomenological, socio‐demographic and psychological features. The 259 participants were recruited from one urban and one rural area in the UK, as part of the UNIQUE (Unusual Experiences Enquiry) study. Results showed that the non‐clinical group experienced hallucinations in all modalities as well as first‐rank symptoms, with an earlier age of onset than in the clinical group. Somatic/tactile hallucinations were more frequent than in the clinical group, while commenting and conversing voices were rare. Participants in the non‐clinical group were differentiated from their clinical counterparts by being less paranoid and deluded, apart from ideas of reference, and having fewer cognitive difficulties and negative symptoms. Unlike the clinical group, they were characterized neither by low psychosocial functioning nor by social adversity. However, childhood trauma featured in both groups. They were similar to the controls in psychological characteristics: they did not report current emotional problems, had intact self‐esteem, displayed healthy schemas about the self and others, showed high life satisfaction and well‐being, and high mindfulness. These findings support biopsychosocial models postulating that environmental and psychological factors interact with biological processes in the aetiology of psychosis. While some PEs may be more malign than others, lower levels of social and environmental adversity, combined with protective factors such as intact IQ, spirituality, and psychological and emotional well‐being, may reduce the likelihood of persistent PEs leading to pathological outcomes. Future research should focus on protective factors and determinants of well‐being in the context of PEs, rather than exclusively on risk factors and biomarkers of disease states.